2004
DOI: 10.1093/carcin/bgh240
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage-related genes AKR1C3 and OGG1 modulate risks for lung cancer due to exposure to PAH-rich coal combustion emissions

Abstract: Lung cancer rates among men and particularly among women, almost all of whom are non-smokers, in Xuan Wei County, China are among the highest in China and have been causally associated with exposure to indoor smoky coal emissions that contain very high levels of polycyclic aromatic hydrocarbons (PAHs). As such, this population provides a unique opportunity to study the pathogenesis of PAH-induced lung cancer that is not substantially influenced by the large number of other carcinogenic constituents of tobacco … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
97
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 27 publications
2
97
2
Order By: Relevance
“…Twenty-one case-control studies examining the effect of NQO1 Pro187Ser polymorphisms on the risk of lung cancer were identified (16,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45); one study was only identified from citation (34), and one was an unpublished study (44). We excluded one study due to the lack of genotype information (37).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one case-control studies examining the effect of NQO1 Pro187Ser polymorphisms on the risk of lung cancer were identified (16,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45); one study was only identified from citation (34), and one was an unpublished study (44). We excluded one study due to the lack of genotype information (37).…”
Section: Resultsmentioning
confidence: 99%
“…Studies indicated a role of the HOGG1 Ser326Cys polymorphism in many cancers including oro-laryngeal cancer (Elahi et al, 2002;Yang et al, 2008), esophageal cancer (Xing et al, 2001), lung cancer (Lan et al, 2004), gastric cancer (Hanaoka et al, 2001), renal cell carcinoma (RCC) (Zhao et al, 2011), gallbladder cancer (Jiao et al, 2007), bladder cancer (Arizono et al, 2008), prostate cancer (Zhang et al, 2010) and acute lymphoblastic leukemia (Stanczyk et al, 2011).…”
mentioning
confidence: 99%
“…The BER enzyme 8-oxoguanine glycosylase (OGG1) repairs 8-OhdG in mammals, and thus preserves genomic integrity and genetic functions. Lan et al (2004) suggested that OGG1 deficiency was associated with an increase in mutations and may participate in carcinogenesis.…”
mentioning
confidence: 99%